The main directions of investment policy in railway transport of Ukraine (Economics and region, 2022)
The article considers the railway transport infrastructure of the country as a system-forming sector of the production infrastructure of the national economy. A number of domestic and foreign scientists who research the problems of investment support for the development of the railway transport infrastructure of the country are listed. Problematic issues of investment development of railway transport, which require further research and development in this direction, are singled out. The role of railway transport, which the specified sector plays in the development of the national economy in modern conditions, is defined. The investment activity in railway transport of Ukraine for the period from 2015 to 2020 was analyzed. An analysis of the volume and structure of capital investments by type of economic activity "Transport, warehousing, postal and courier activity" in Ukraine for the period from 2015 to 2020 was carried out. Private sources of financing investments in the development of the country's railway transport infrastructure in modern conditions are singled out. The influence of the railway transport infrastructure sector of the country on increasing the efficiency of the development of the national economy as a whole at the current stage of development is outlined. Individual infrastructure investment projects in the country's railway transport planned for 2020 are highlighted. The volume of capital investments of the Joint Stock Company "Ukrzaliznytsia" and their structure by main directions for the period 2016-2020 have been analyzed. The assessment of the possibilities of attracting investments in the development of railway transport from various sources of financing is given. The key provisions are defined and the scheme of the system software for the development of the railway transport infrastructure of the country and the ways of their implementation in modern conditions are proposed.
Keywords: railway transport; railway transport infrastructure; investment activity; software; system reform; реформування системи